2016
DOI: 10.1016/j.actbio.2016.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of thoracic aortic aneurysm rupture in vitro

Abstract: A major challenge in the experimental study of aneurysm properties is that the tissues are heterogeneous. When the specimens are not reasonably homogeneous, traditional tests that work under the premise of tissue homogeneity cannot reliably delineate the local conditions at the rupture site. In this work, we investigated the local characteristics of rupture of human ascending aortic aneurysm tissue. We identified the stress, strain, and elastic properties to a submillimeter resolution. Based on the field value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…This correlation opens the possibility of estimating the strength from in vivo response or using the yielding parameter as a surrogate. In a recent study, the present authors found that ATAA samples rupture uniformly in the direction of maximum stiffness, showing a strong directional correlation. For ATAA tissue (and alike), it is reasonable to hypothesize that correlation exists between the strength (that is, the stress at rupture) and response characteristics prior to rupture.…”
Section: Introductionmentioning
confidence: 49%
See 3 more Smart Citations
“…This correlation opens the possibility of estimating the strength from in vivo response or using the yielding parameter as a surrogate. In a recent study, the present authors found that ATAA samples rupture uniformly in the direction of maximum stiffness, showing a strong directional correlation. For ATAA tissue (and alike), it is reasonable to hypothesize that correlation exists between the strength (that is, the stress at rupture) and response characteristics prior to rupture.…”
Section: Introductionmentioning
confidence: 49%
“…Tension‐strain curves were obtained using inflation test and a pointwise identification method . Ascending thoracic aortic aneurysm samples were collected from patients undergoing surgery repair, in accordance with a protocol approved by the local institutional review board.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…where (19) is the fourth-order elasticity tensor. Intact material can propagate waves and, consequently,…”
Section: Loss Of Ellipticity and Crack Directionmentioning
confidence: 99%